COVID-19 Vaccines - Sibel Yıldız Kaya; Abdurrahman Kaya; Birgül Mete (Cam & Sakura Medical Journal, 2023)
The novel coronavirus is an infectious disease caused by severe acute respiratory syndrome coronavirus-2. The World Health Organization declared coronavirus disease-2019 (COVID-19) outbreak is a pandemic in 2020. Many people die of acute respiratory failure both in community and hospital. Therefore, there is an urgent need for a novel effective treatment or vaccine to combat the outbreak. To develop new vaccine, a wide variety of studies have been conducted in many countries. Some vaccines are approved by the Food and Drug Administration. They were developed by a vari-ety of techniques; mRNA, inactivated, recombinant and vector-based vaccines. Most of them are safe and effective, but some adverse reactions have been observed. COVID-19 vaccination prevented spread of the virus and halted the outbreak, by breaking the chain of the infection. Thus, the pan-demic has proven again that vaccination is essential for human health. In this article, we attempted to review the commonly used ones in clinical practice.